2018
DOI: 10.1049/iet-epa.2018.5180
|View full text |Cite
|
Sign up to set email alerts
|

Direct torque control of a permanent magnet synchronous machine for hybrid hydraulic excavator

Abstract: A hybrid power train system (HPTS) is considered as a promising technology to improve the efficiency of excavators. In the hybrid hydraulic excavator, due to the drastic changes in the load, ultra-capacitors are employed to realise fast charge and discharge. Accordingly, a wide change of the DC voltage will happen. When the DC voltage is small, the maximum torque that the electric machine can output will be limited. The electric machine cannot fully compensate for the engine torque. Therefore, a novel direct t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Apply Laplace transform to equations (2) and 3to obtain the transfer function of pressure and flow of the pump outlet.…”
Section: A Mathematical Model Analysis Of Electric Motor-pumpmentioning
confidence: 99%
See 1 more Smart Citation
“…Apply Laplace transform to equations (2) and 3to obtain the transfer function of pressure and flow of the pump outlet.…”
Section: A Mathematical Model Analysis Of Electric Motor-pumpmentioning
confidence: 99%
“…Chen et al designed a power motor according to the working characteristics of hybrid CM, and tested the motor control method by adopting the vector control. The results showed that the dynamic characteristics of the power system and the energy savings of the system were improved [2]. Han et al employed a motor to replace the hydraulic motor of the hybrid excavator.…”
Section: Introductionmentioning
confidence: 99%
“…The application of hybrid technology and energy recovery technology in hydraulic excavators is divided into two categories. One is an electric hybrid excavator, and the other is a hydraulic hybrid excavator [17,18] . The energy storage unit of an electric hybrid excavator is a battery or ultracapacitor.…”
Section: Introductionmentioning
confidence: 99%
“…When the energy is reused, the electrical energy is converted into hydraulic energy, which drives the hydraulic pump to work. The energy storage unit of the hydraulic hybrid excavator is a hydraulic accumulator [18] . The hydraulic accumulator stores the boom potential energy and rotational kinetic energy in the form of hydraulic energy.…”
Section: Introductionmentioning
confidence: 99%
“…The simple structure of permanent magnet synchronous motors (PMSMs) combined with their useful features like high efficiency and high power‐density make them ideal for use in aerospace applications, transportation and industrial manufacturing [1–3]. It is possible to vary the air‐gap magnetic flux density, back electromotive force and torque characteristic of the motor using different types of stator slots.…”
Section: Introductionmentioning
confidence: 99%